Dealing with the statute of limitation in claims for damages arising out of antitrust infringements - Poch, Albert (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The transposition into Spanish legislation of Directive 2014/104/EU, by Royal Decree-Law 9/2017, has made important progress in the regulation of the statute of limitation in actions for damages arising out of antitrust infringements. Despite the undeniable benefits that the new regulation has provided in terms of legal certainty, this article will examine the doubts that currently persist as a result of the transitory regime, as well as the eventual ineffectiveness of the regulation of the prescription provided in the Civil Code, in order to compensate the victims of an antitrust infringements ex Article 101 and 102 FTEU.
Keywords: private enforcement; damages actions; damages Directive; statute of limitation; follow- on claims; Cogeco